Fake news in Virtual Environments - Ribeiro, Vitor de Almeida; Monica Cristina Servidoni (Revista Interface Tecnológica, 2022)
The number of users in virtual environments has grown in the last decades allowing the interaction of people who are close to each other or have a common taste. Linked to this growth, the amount of content published, shared, or forwarded has increased, making fraudulent content easily reach users prone to receive it. The fight against fake news is an obligation of users, platforms, authorities, and institutions. However, the Superior Electoral Court, concerned about the approach of the elections, has been requesting social networks and private messaging services to take actions to prevent the dissemination of fake news within their platforms. The present article has the objective of verifying the actions taken to reduce the number of fake news circulating in virtual environments, based on a literature review. Finally, considering the actions raised in the article, it was evident that social networks and instant messaging services, even with limited legal support, are reducing the reach or removing fraudulent content based on complaints from users, in addition to using their own technology available to be able to analyze the largest number of publications on the network, which would take a long time if performed by a human.
Keywords: Fake news; Virtual environment; Democracy